Complications of surgical port-a-cath implantation in paediatric patients: a single institution experience - Saeed Al Hindi; Zahra Khalaf; Abigail K. L. Tan; Fayza Haider (SpringerOpen, 2022)
Abstract Background Implantable vascular access devices (IVADs) provide durable routes for administering long-term treatments in patients. However, their associated complications pose a problem. One technique variation that can influence complication rates is the method of securing the IVADs, which is either by ligation or a purse-string suture. Objective To compare the two port-a-cath securing techniques, ligation and purse string, in terms of complication rates and types. Study design We prospectively included 67 paediatric patients who had port-a-cath insertions secured either by ligation or a purse-string suture at Salmaniya Medical Complex in Bahrain from January 2018 to June 2021. We recorded demographics, diagnoses, port-a-cath site of insertion and securing technique, operative time, follow-up duration, and complications. Patients who had previous port-a-cath insertions or other chemotherapy lines were excluded. Results Port-a-caths were secured by ligation in 35 cases and by a purse-string suture in 32 cases. There were 58.9% males and 41.8% females; sex was not correlated with complications (P = 0.11). Patients' ages ranged from 2 months to 13 years. The overall complication rate of port-a-cath insertions was 16.42%. Complications occurred in 25.7% of ligation-secured port-a-caths and 6.3% of purse-string-secured port-a-caths. In the ligation-secured IVADs, complications included malfunction, infections, removal difficulty and blockage, malposition, and haematoma. Meanwhile, only leakage occurred in the purse-string-secured IVADs. Conclusion The port-a-cath securing technique was significantly correlated with complication rates. The complication types and rates in purse-string-secured catheters were lower than those reported in the literature. Leakage was the only complication that occurred in purse-string-secured port-a-caths.